Analisis Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan Barang Konsumsi di BEI tahun 2002 – 2011 - Andi Yoshendy; Noer A. Achsani; TB N. A. Maulana (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
The objective of this empirical study is to explore factors affecting the capital structure of consumer goods manufacturing companies and to investigate whether the capital structure models based on prior researches provide convincing explanations for capital structure decisions of the Indonesian companies.We reviewed several capital structure theories (the trade-off theory, pecking order theory, agency theory, and signaling theory) to identify factors that determines capital structure for consumer goods companies in Indonesia. The research was conducted using panel data procedures for a sample of 29 companies that listed on the Indonesian Stock Exchange during 20022011.The findings suggest that profitability and tangibility are related negatively to the debt ratio, size and age are related positively to the debt ratio, while non-debt tax shields and liquidity do not appear to be related to debt ratio. The findings support mostly the pecking order theory to explain the capital structure of Indonesian consumer goods manufacturing companies. The findings of this research also clearly demonstrate the importance of capital structure decisions for financial management. This can help managers to make optimal capital structure decisions.